Applying the recovery approach to the interface between mental health and child protection services. Issue 1 (2nd January 2016) - Duffy, Joe; Davidson, Gavin; Kavanagh, Damien
ABSTRACT: There is a range of theoretical approaches which may inform the interface between child protection and adult mental health services. These theoretical perspectives tend to be focused on either child protection or mental health with no agreed integrating framework. The interface continues to be identified, in research, case management reviews and inquiry reports, as complex and problematic. This article proposes that more positive, integrated approaches to service user engagement, risk assessment and management may lead to better outcomes in working with families experiencing parental mental health problems and child protection concerns. It is proposed that the recovery approach, increasingly used in mental health services, can inform the processes of engagement, assessment and intervention at the mental health and child protection interface. The article provides a critical overview of the recovery approach and compares it with approaches typifying interventions in child protection work to date. Relevant research and inquiries are also examined as a context for how to more effectively respond to cases where there are issues around parental mental health problems and child protection. The article concludes with case material to illustrate the potential application of the recovery approach to the interface between mental health and child protection services.